Is transhumanism the solution to euthanasia? - Bugajska, Anna (Array, 2021)
The article concentrates on the question of euthanasia in relation to the emerging  life-extension technologies and the immortality industry within the philosophical framework of transhumanism. I begin by sketching the picture of human enhancement and immortality research and industry and pointing to its preliminary assessment of social impact, drawn by Jacobsen (2017). I present immortalism as a specific branch of transhumanism, leading to the rise of postmortal society informed by neohedonism and negative utilitarianism: oriented towards the pursuit of pleasure and minimization of suffering. I ask the question if in the postmortal society the problem of euthanasia will exist. To answer this question, firstly, I briefly present the changes in understanding the notion of a good death; secondly, I discuss the transhumanist approach to euthanasia. And thirdly, I point to the challenges to the biopolitics of death and dying in the postmortal society. The discussion of these areas leads to the conclusion that the problem of euthanasia in the postmortal society will not disappear; rather, it will become more aggravated due to the paradoxical nature of the transhumanist approach to death, personal freedom, autonomy, and dignity.